Strategi Inovatif Pengembangan Usaha Spa Lokal Melalui Pendekatan Businsess Model Canvas (BMC) di Desa Wisata Nglanggeran - Faline, Faline (Islamic Management and Empowerment Journal, 2025)
This research aims to analyze the business development strategy of Griya Spa Purba Ayu in Nglanggeran Tourism Village through the Business Model Canvas (BMC) approach. This research is important because Griya Spa is an example of community-based economic empowerment that empowers local women in the traditional spa service sector. The method used is a qualitative approach with interview, observation, and focus group discussion (FGD) techniques. The results showed that Griya Spa has an advantage in the aspect of value proposition based on local wisdom, but still faces challenges in managing promotional channels and customer relations. This research provides recommendations for homecare service development programs, co-creation training, and digitalization of customer management to strengthen Griya Spa's position as a leading ecotourism destination. The findings are expected to be a reference in the development of local tourism-based MSMEs.